AQUACISION: a multiparameter aquaculture water quality ester and decision support system - Mark Anthony A. Lazo; Louise Mark Kit S. Geronimo; Lester John T. Comilang; Kenneth John B. Cayme; Jay M. Ventura; Ertie C. Abana (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The paper presents a multiparameter aquaculture water quality tester with a decision support system. A device was developed to aid aquaculture farmers in monitoring water quality parameters and maintaining or achieving optimal levels by suggesting ways on how a farmer can respond to such measurements. The AQUACISION device measures six different water quality parameters; temperature, practical salinity, pH level, total dissolved solid (TDS), oxidation-reduction potential (ORP), and algae density. Measurements were sent to the AQUACISION application where they were processed to determine the course of action that was best to maintain or achieve optimal levels using fuzzy rules. Based on the comparative result, the AQUACISION was accurate in measuring temperature, practical salinity, pH level, TDS, and ORP during the actual testing. The application also received an excellent rating on the ISO/IEC 25010 software quality model standard